Comprehending expository texts: the dynamic neurobiological correlates of building a coherent text representation - Miller, Amanda; Swett, Katherine; Burns, Scott; Davis, Nicole; Hoeft, Fumiko; Petrill, Stephen A.; Cutting, Laurie E. (Frontiers in Human Neuroscience, 2013)
Little is known about the neural correlates of expository text comprehension. In this study, we sought to identify neural networks underlying expository text comprehension, how those networks change over the course of comprehension, and whether information central to the overall meaning of the text is functionally distinct from peripheral information. Seventeen adult subjects read expository passages while being scanned using functional magnetic resonance imaging (fMRI). By convolving phrase onsets with the hemodynamic response function (HRF), we were able to identify regions that increase and decrease in activation over the course of passage comprehension. We found that expository text comprehension relies on the co-activation of the semantic control network and regions in the posterior midline previously associated with mental model updating and integration (posterior cingulate cortex (PCC) and precuneus (PCU)). When compared to single word comprehension, left PCC and left Angular Gyrus (AG) were activated only for discourse-level comprehension. Over the course of comprehension, reliance on the same regions in the semantic control network and posterior midline increased, while a parietal region associated with attention (intraparietal sulcus (IPS)) decreased. These results parallel previous findings in narrative comprehension that the initial stages of mental model building require greater visuospatial attention processes, while maintenance of the model increasingly relies on semantic integration regions. Additionally, we used an event-related analysis to examine phrases central to the text’s overall meaning versus peripheral phrases. It was found that central ideas are functionally distinct from peripheral (showing greater activation in the PCC and PCU), and also recruit different parts of the semantic control network over time than peripheral ideas. These findings support previous behavioral models on the cognitive importance of distinguishing textual centrality